Still with me?: assessing the persisting relationship to a deceased loved-one : validation of the “Continuing Bonds Scale” in a German population - Hopf, Dora; Eckstein, Monika; Ditzen, Beate; Aguilar-Raab, Corina (Omega, 2022)
Continuing the bond (CB) to a deceased loved one plays a clinically significant role in grief. We validated the Continuing Bonds Scale (CBS) examining externalized CB (illusions and hallucinations) versus internalized CB (use of the deceased as a secure base) in relation to risk factors of complicated grief and bereavement-related adjustment. Data from 364 bereaved German participants on CBS, Inventory of Complicated Grief (ICG), and Posttraumatic Personal Growth Inventory (PPGI) entered an exploratory factor analysis. This yielded a two-factor-solution representing externalized and internalized CB (KMO = .89, ?2 = 2100.5, df = 120). Both factors demonstrated high internal consistency (Cronbach's α = .87). ICG and PPGI highly correlated with externalized and internalized CB. Cause of death and feelings of responsibility were associated with externalized CB. In the future, the use of the CBS could help predict problems in grief processing and consequently implement early interventions.
Gesehen am 20.03.2023